Progressive familial intrahepatic cholestasis—outcome and time to transplant after biliary diversion according to genetic subtypes - Sahloul, Abdulla; Lainka, Elke; Kathemann, Simone; Swoboda, Sandra; Dröge, Carola; Keitel, Verena; Al-Matary, Yahya Saleh; Berger, Michael; Schulze, Maren (Frontiers in Surgery, 2023)
Background: Progressive familial intrahepatic cholestasis (PFIC) is a heterogeneous disease characterized by progressive cholestasis in early childhood. Surgical therapy aims in preventing bile absorption either by external or internal biliary diversion (BD). Several different genetic subtypes encode for defects in bile transport proteins, and new subtypes are being discovered ongoingly. Overall, the literature is scarce, however, accumulating evidence points to PFIC 2 having a more aggressive course and to respond less favorable to BD. With this knowledge, we aimed to retrospectively analyze the long-term outcome of PFIC 2 compared to PFIC 1 following BD in children at our center. Methods: Clinical data and laboratory findings of all children with PFIC (n = 40), who were treated and managed in our hospital between 1993 and 2022, were analyzed retrospectively. Results: Overall, we treated 40 children with PFIC Type I (n = 10), Type II (n = 20) and Type III (n = 10). Biliary diversion was performed in 13 children (with PFIC 1, n = 6 and II, n = 7). Following BD, bile acids (BA) (p = 0.0002), cholesterol (p < 0.0001) and triglyceride (p < 0.0001) levels significantly decreased only in children with PFIC 1 but not in PFIC 2. Three out of 6 children (50%) with PFIC 1 and 4 out of 7 children (57%) with PFIC 2 required liver transplantation despite undergoing BD. On an individual case basis, BA reduction following BD predicted this outcome. Of the 10 children who had PFIC 3, none had biliary diversion and 7 (70%) required liver transplantation. Conclusion: In our cohort, biliary diversion was effective in decreasing bile acids, cholesterol levels as well as triglycerides in the serum only in children with PFIC 1 but not PFIC 2. On an individual case level, a decrease in BA following BD predicted the need for liver transplantation.